Sulfurization- Desulfurization of Iron-Calcium Oxygen Carriers during Chemical Looping Combustion of Syngas - Yu-Lun Chen; Young Ku; Ya-Chun Chang (Aerosol and Air Quality Research)
Abstract Chemical looping combustion of SO2-containing syngas with various fabricated iron-calcium oxygen carriers was studied to comprehend the sulfurization and desulfurization of oxygen carriers during combustion. Experimental results indicated calcium-iron oxygen carriers fabricated with CaO:Fe2O3 weight ratio of 3:7 and calcined at 800°C (CaFe-378) was suitable for chemical looping combustion of syngas. CaFe2O4 was noticed to be the dominant crystalline phase in CaFe-378 even after 10 redox operations. Reduction kinetics for chemical looping combustion of both H2 or CO in syngas with CaFe-378 were adequately described by the 2-dimension diffusion model. The activation energies of H2 and CO with CaFe-378 were determined to be 35.4 kJ mol−1 and 46.0 kJ mol−1, respectively. Calcium sulfide (CaS) was generated during the chemical looping combustion of SO2-containing syngas with CaFe-378. CaS was further oxidized to CaSO4 on the surface of CaFe-378 during air regeneration, which might inhibit the complete regeneration of iron oxides. Satisfactory regeneration of sulfurized oxygen carriers was accomplished by introducing hydrogen after the air-regeneration because of the reduction of calcium sulfate to calcium oxide.